Development of Physics Learning Module Based on Industrial Vocational Era Era 4.0 to Improve Student Learning Skills in SMK. Issue 4 (March 2020) - Darwis; Lubis, A M; Pasaribu, M; Sormin, A S; Ansari, R
Abstract: The research conducted to produce a physics-based learning module vocational industry the 4.0 era to improve vocational students learning skills — research techniques implemented by the research development research method and. The results of the study include the development of physics modules based on industry era learning skills 4.0. The feasibility standard for the results of physics learning modules based on industrial vocations in the 4.0 era can be seen from the validators assessment and student response to improving student learning skills. Improvement of students learning skills can be seen based on a questionnaire and observation of learning activities students in physics. Research on the development of physics learning modules based on industrial vocational era 4.0 can be used to improve student learning skills in physics material in Vocational High Schools (SMK). The application modules based on the industrial vocational industry 4.0 era is a media solution and a reference for physics teachers in vocational high schools. The results of the study show that industrial vocational-based physics learning modules in the 4.0 era can improve responses and improve student concentration in learning physics material in vocational high schools.